Benchmarks for Submerged Structure Response to Underwater Explosions - Hans U. Mair (Shock and Vibration)
Benchmarks for submerged structure response to underwater explosions (UNDEX) are compiled. Both analytical and empirical benchmarks are presented; each type has advantages and disadvantages for the purposes of model validation, though no methodology for employing these benchmarks in a model validation effort is proposed. Benchmark computations are also referenced as part of this compilation. Finally, extension of this compilation to the UNDEX response of internal equipment and floating structures, and to hydrodynamic/hydraulic ram problems, is proposed.